Content-sensitive Approach for Video Browsing and Retrieval in the Context of Video Delivery: VBaR Framework - Lau, P.Y.; Park, S. (Informatica)
Content-sensitive Approach for Video Browsing and Retrieval in the Context of Video Delivery: VBaR Framework